1988
DOI: 10.1152/ajpregu.1988.254.3.r431
|View full text |Cite
|
Sign up to set email alerts
|

Renin, ACTH, and aldosterone during acute hypercapnia and hypoxia in conscious rats

Abstract: The control of aldosterone secretion may be altered during acute changes in arterial blood gases. We studied the blood gas, plasma electrolyte, renin (PRA), adrenocorticotropic hormone (ACTH), and aldosterone (ALDO) responses to acute hypercapnia (4 and 8% CO2), acute hypocapnic hypoxia (10% O2), acute severe normocapnic hypoxia (7% O2-4% CO2), and acute hypercapnic hypoxia (7% O2-8% CO2) in conscious, cannulated Long-Evans rats. Normoxia resulted in normal levels of PRA (6.9 +/- 2.0 ng.ml-1.h-1), ACTH (96 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
3
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 15 publications
1
43
3
1
Order By: Relevance
“…As soon as a litter was completely delivered, the pups were weighed and cross-fostered (8-10 pups/dam), and the dam and its pups were moved to an environmental chamber and exposed to normobaric normoxia (21% O 2) or hypoxia (12% O2) as described in detail previously (28,36). We have previously shown that this exposure leads to arterial PO 2 levels in adults of about 50-55 Torr with sustained respiratory alkalosis with metabolic compensation (27,30,31).…”
Section: Animal Treatment and Exposure To Hypoxiamentioning
confidence: 99%
“…As soon as a litter was completely delivered, the pups were weighed and cross-fostered (8-10 pups/dam), and the dam and its pups were moved to an environmental chamber and exposed to normobaric normoxia (21% O 2) or hypoxia (12% O2) as described in detail previously (28,36). We have previously shown that this exposure leads to arterial PO 2 levels in adults of about 50-55 Torr with sustained respiratory alkalosis with metabolic compensation (27,30,31).…”
Section: Animal Treatment and Exposure To Hypoxiamentioning
confidence: 99%
“…Hypoxia is a systemic stress that can activate the HPA axis (22,43). CORT levels increased following hypoxia, but, given their differences in HPA axis function, the lack of differences between NMS and control rats in this response was unexpected.…”
Section: Interactions Between Gonadotropic and Corticotropic Axes Andmentioning
confidence: 99%
“…pH o ) has a modulatory role in the control of aldosterone secretion arose from correlations between plasma aldosterone concentration and acid-base status (Christleib et al 1975, Kassirer et al 1976, Perez et al 1977, 1979, Schambelan & Sebastian 1977, Scott et al 1978, Raff & Roarty 1988, Julian et al 1982. The premise developed further in light of the ability of alterations in pH o to affect aldosterone secretion in vitro (Muller 1965, Chiu & Freer 1979, Gilchrist et al 1983 Carroll et al 1986, Radke et al 1986a.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aldosterone levels in plasma increased during diabetic ketoacidosis (Christlieb et al 1975, Scott et al 1978, Quigley et al 1982, metabolic acidosis (Perez et al 1977, 1979, Schambelan & Sebastian 1977 and acute respiratory acidosis (Raff & Roarty 1988). Conversely, during metabolic alkalosis (Kassirer et al 1967, Julian et al 1982, plasma aldosterone concentration decreased.…”
Section: Introductionmentioning
confidence: 99%